2001
DOI: 10.1021/ja011450+
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of High-Spin Iron(III)−Alkylperoxo Complexes and Its Relation to Low-Spin Analogues:  Reaction Coordinate of O−O Bond Homolysis

Abstract: The spectroscopic properties of the high-spin Fe(III)-alkylperoxo model complex [Fe(6-Me(3)TPA)(OH(x))(OO(t)Bu)](x)(+) (1; TPA = tris(2-pyridylmethyl)amine, (t)Bu = tert-butyl, x = 1 or 2) are defined and related to density functional calculations of corresponding models in order to determine the electronic structure and reactivity of this system. The Raman spectra of 1 show four peaks at 876, 842, 637, and 469 cm(-1) that are assigned with the help of normal coordinate analysis, and corresponding force consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
262
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(297 citation statements)
references
References 50 publications
32
262
3
Order By: Relevance
“…On the basis of the differences in the bonding that are apparent from the vibrational studies of S ϭ 1͞2 and S ϭ 3͞2 {FeNO} 7 , a high-spin ferric (hydro)peroxo intermediate is likely to be essential to promote breakdown via Fe-O rather O-O bond cleavage. This is in accord with recent studies by the Solomon and Que groups, which have shown that high-spin Fe 3ϩ -(alkyl)peroxo have much weaker Fe-O bonds and much stronger O-O bonds than their low-spin counterparts (43,44). Overall, characterization of the NO adducts of SOR indicates that the Fe spin state and the trans cysteinate ligand play important roles in effecting superoxide reduction and peroxide release at the SOR active site.…”
Section: Discussionsupporting
confidence: 89%
“…On the basis of the differences in the bonding that are apparent from the vibrational studies of S ϭ 1͞2 and S ϭ 3͞2 {FeNO} 7 , a high-spin ferric (hydro)peroxo intermediate is likely to be essential to promote breakdown via Fe-O rather O-O bond cleavage. This is in accord with recent studies by the Solomon and Que groups, which have shown that high-spin Fe 3ϩ -(alkyl)peroxo have much weaker Fe-O bonds and much stronger O-O bonds than their low-spin counterparts (43,44). Overall, characterization of the NO adducts of SOR indicates that the Fe spin state and the trans cysteinate ligand play important roles in effecting superoxide reduction and peroxide release at the SOR active site.…”
Section: Discussionsupporting
confidence: 89%
“…In line with DFT calculations, [35][36][37] the low-spin iron(III) center plays a role in weakening the O-O bond and priming it for homolysis prior to substrate attack, a reactivity documented for 1a. 71 Comparison of 1a with activated bleomycin reveals major spectroscopic differences between the two complexes.…”
Section: Summary and Perspectivementioning
confidence: 66%
“…These features have been assigned to a ν(Fe-O 2 H) and a ν(O-O) vibration, respectively, and are considered to be the Raman signature of a low-spin Fe III -OOH intermediate. 20,24 In contrast, almost all high-spin mono-and diiron(III)-peroxo complexes typically exhibit [ [35][36][37] In support, Figure 3B shows the linear correlation between the ν(O-O) and the redox potential of the parent Fe II complex with ν(O-O) decreasing with redox potential. Thus, stabilization of the iron(III) oxidation state due to greater electron density at the metal center weakens the O-O bond.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…5 bottom § The complete bleomycin ligand also includes a sugar moiety, a ␤-aminoalanine fragment, and a bithiazole tail. (33)(34)(35). From the homolysis calculations in Table 2 Left, the reaction energy ⌬E is much less sensitive to the ligand type, and the solvation effects are small.…”
mentioning
confidence: 99%